125IODINE BRACHYTHERAPY IN THE TREATMENT OF MALIGNANT ORBITAL TUMORS AS A POSSIBLE ALTERNATIVE TO TELEIRRADIATION - A. A. Yarovoy; O. V. Golubeva (Опухоли головы и шеи, 2015)
The overview of single publications on brachytherapy (BT) for orbital tumors generates only a shallow idea of the technique. In spite of attempts to clinically use BT, many questions remain to be further discussed and investigated; these are how to draw an individual plan for orbital tumor irradiation; what program should be used to plan BT; which dosage load should be applied to the structure of the orbit and eye, and many other questions. Experimental studies are a necessary stage to solving the arising problems and tasks related to BT for orbital tumors. The calculations have shown that 125I BT is a possible alternative to teleradiotherapy for malignant orbital tumors in terms of dosimetry and technical feasibility.